Oropharyngeal exercises to reduce symptoms of OSA after AT - Villa, Maria Pia; Brasili, Luca; Ferretti, Alessandro; Vitelli, Ottavio; Rabasco, Jole; Mazzotta, Anna Rita; Pietropaoli, Nicoletta; Martella, Susy (Sleep & breathing, 2015)
Purpose This study evaluated the efficacy of oropharyngeal exercises in children with symptoms of obstructive sleep apnea syndrome (OSA) after adenotonsillectomy. Methods Polysomnographic recordings were performed before adenotonsillectomy and 6 months after surgery. Patients with residual OSA (apnea-Hypopnea Index, AHI > 1 and persistence of respiratory symptoms) after adenotonsillectomy were randomized either to a group treated with oropharyngeal exercises (group 1) or to a control group (group 2). A morphofunctional evaluation with Glatzel and Rosenthal tests was performed before and after 2 months of exercises. All the subjects were re-evaluated after exercise through polysomnography and clinical evaluation. The improvement in OSA was defined by ΔAHI: (AHI at T1 − AHI at T2)/AHI at T1 × 100. Results Group 1 was composed of 14 subjects (mean age, 6.01 ± 1.55) while group 2 was composed of 13 subjects (mean age, 5.76 ± 0.82). The AHI was 16.79 ± 9.34 before adenotonsillectomy and 4.72 ± 3.04 after surgery ( p < 0.001). The ΔAHI was significantly higher in group 1 (58.01 %; range from 40.51 to 75.51 %) than in group 2 (6.96 %; range from −23.04 to 36.96 %). Morphofunctional evaluation demonstrated a reduction in oral breathing ( p = 0.002), positive Glatzel test ( p < 0.05), positive Rosenthal test ( p < 0.05), and increased labial seal ( p < 0.001), and lip tone ( p < 0.05). Conclusions Oropharyngeal exercises may be considered as complementary therapy to adenotonsillectomy to effectively treat pediatric OSA.